TINJAUAN KETEPATAN KODEFIKASI DIAGNOSA UTAMA RAWAT INAP KASUS DIABETES MELLITUS DI RSUD KOJA - Hari Rinaldi; Deasy Rosmala Dewi; Nanda Aula Rumana; Muniroh Muniroh (Journal of Innovation Research and Knowledge, 2022)
Coding officers must understand their roles and duties in generating accurate codes for reporting data in order to produce useful information. The coding of the diagnosis must be correct, because if it is not correct it will affect the management of clinical data, billing costs, and other matters related to health care care. Based on this, the researchers conducted a study on the accuracy of the diagnosis code at Koja Hospital by taking cases of Diabetes Mellitus inpatients in 2020. The purpose of this study was to get an overview of the accuracy of coding the diagnosis of Diabetes Mellitus cases in 2020 and identify the SOP for Code Giving at Koja Hospital. The research started from October - December 2020. The research method is a descriptive method. Researchers took 60 samples obtained using the Slovin formula. From a total of 60 samples studied, there are 51 (85%) medical record documents that are correct in coding and there are 9 (15%) medical record documents that are not correct in coding. It can be concluded that the coding of the diagnosis of Diabetes Mellitus in Koja Hospital is high. However, there are still some errors in coding. The main factor that becomes an obstacle is the communication factor of the medical record officer in the coding section with the nurse or doctor. It is better for the coding officer to establish more communication if there is a diagnosis that is not understood.